SIMPLIFIKASI SISTEM DAN PROSEDUR DI PELABUHAN DAPAT MENGURANGI CELAH PENYIMPANGAN DAN EKONOMI BIAYA TINGGI - Iswanto Iswanto (Sekolah Tinggi Maritim Yogyakarta, 2015)
Port as a gateway, interface and become links in and out of goods bothregionally and internationally has a current density of services a very high,ranging from maintenance to come goings of ships, entry and exit of goods aswell as the utilization of existing facilities at the port, either by means ofcompulsory and only when needed , from hardware and software. The density ofthe maintenance of this service requires a long bureaucratic and everything isalmost in the form of a monopoly or near-monopoly at risk of fraud, since allservice users want quick service, which is generally to avoid high-cost economy,the condition of this kind must be overcome to prepare the system andprocedures either to eliminate the negative image of the harbor, m bureaucraticbarriers, and can also be reached by entrepreneurs bureaucracy, by changingthe mental attitude of bureaucrats to focus on the goals, improve the system ofreward, so that the organization is performing well, along with a control strategyby using rules that detail well as using culture that can touch feeling and canchange the minds of the organization, which eventually can strengthen newpositive behavior, so that the direction the organization is clear and can achievethe expected goals.